Photovoltaics and Electrification in Agriculture - Muñoz-García, Miguel-Ángel; Hernández-Callejo, Luis (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Integration of photovoltaics and electrification in agriculture. Works on the integration of photovoltaics in agriculture, as well as electrification and microgrids in agriculture. In addition, some works on sustainability in agriculture are added.